(3eHGOF GdGOGQI (B/s - (3GdYdGb, HTjQs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2008)
(3WHjYI GdYedjI GdGOGQjI h JWhQ GdacQ GdGOGQj , YedjI GdGOGQI hhXGFagG , GdYedjI GdJNWjWjI , GdYedjI GdQbGHjI , GdJfXje , GdJfSjb , GdJTcjd , GdJhLjg (B.s
(3eQGLY U(B.251 (3;bGFeI GdeUWdMGJ U(B.219s
Keywords: (3GdGOGQIs; (3GdJfXjes; (3GdQbGHIs